Evidence Mercury May Be an Etiological Factor in Multiple Sclerosis - Robert Siblerud; Joachim Mutter (New Innovations in Chemistry and Biochemistry Vol. 8, 2022)
Mercury is one of the most dangerous metals, capable of causing a wide range of health issues. The goal of this study was to see if mercury may be the cause of multiple sclerosis (MS) by comparing 88 MS-related characteristics to mercury. The findings revealed that all but five factors could be linked to mercury, with the remaining five factors having insufficient evidence to be linked to mercury in one way or another. Nerve demyelination is a hallmark of MS, and mercury is known to cause nerve demyelination. Similar physiological and pathological changes occur in MS and mercury toxicity including those changes involved with the basal ganglia, Bell’s palsy, brain atrophy and shrinkage, brain scarring, dysmetria, myelin basic protein, myelin oliodendrocytes, glycoprotein, oligoclonal bands, oligodendrocytes, ciliary neutrophil factor, white matter, axon and myelin damage, electroencephlography, and brainstem auditory evoked potentials. Similar changes also occur in the immune system including autoimmunity, cytokine changes, gamma globulins, Epstein Barr virus, T cells, herpes virus, and urinary infections. Hormones and biochemistry, such as myelin basic protein, myelin oliodendrocytes, glycoprotein, estriol, free radicals, glial cells, glucosteroids, female hormones, and inrerferon, show similar modifications. The study found that all 32 physical symptoms of MS, as well as all 7 mental health symptoms and all 11 ocular symptoms, could be explained by mercury exposure. The researchers theorised that persons living in southern latitudes are exposed to the sun more, and that the greater amounts of vitamin D, which is anti-inflammatory, may help to counteract mercury-induced inflammation. There is a link between MS and dental caries and dental amalgams, according to studies. According to the WHO, dental amalgams are the most common source of mercury. Mercury is most likely an etiological factor in multiple sclerosis, according to the study.